2015
DOI: 10.5539/gjhs.v8n6p179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Combined Copying Skills Training and Pharmacological Therapy for Patients with Migraine

Abstract: Headache is one of the most common complaints in neurological clinics. The current study carried out to determine the benefits of combined Coping Skills Training (CST) and Pharmacotherapy (Ph) for patients with migraine. Forty patients with migraine recruited from the outpatient clinics of Zahedan University of Medical Sciences(Iran) and randomly assigned to one of two treatment groups: the first group received combined coping skills training (CST) and pharmacotherapy(Ph); and the second group received the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…55 A small randomized controlled trial in adults with migraine showed that the combination of coping skills training plus pharmacotherapy was superior to pharmacotherapy alone in improving self-efficacy. 56 In a pediatric sample of primary headache patients, 3 Internet-based interventions, that is, an educational program, applied relaxation, and a cognitive behavioral therapy program, resulted in improved headache outcomes and pain catastrophizing. 41 Our finding that children and adolescents with migraine cope differently with pain and catastrophize more about pain than controls validates the need for further study into the role of pain coping and catastrophizing in the treatment of pediatric migraine.…”
Section: Discussionmentioning
confidence: 99%
“…55 A small randomized controlled trial in adults with migraine showed that the combination of coping skills training plus pharmacotherapy was superior to pharmacotherapy alone in improving self-efficacy. 56 In a pediatric sample of primary headache patients, 3 Internet-based interventions, that is, an educational program, applied relaxation, and a cognitive behavioral therapy program, resulted in improved headache outcomes and pain catastrophizing. 41 Our finding that children and adolescents with migraine cope differently with pain and catastrophize more about pain than controls validates the need for further study into the role of pain coping and catastrophizing in the treatment of pediatric migraine.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQOL-BREF is a frequently used instrument for the assessment of HRQOL. Although applied for the assessment of HRQOL among individuals with headache disorders [16][17][18][19], little is known about its psychometric properties. The present study examined the reliability and factor structure of the questionnaire in individuals with chronic headache in Austria and its equivalence between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQOL-BREF has been frequently used to examine the HRQOL of patients with different chronic conditions, including headache disorders [16][17][18][19]. Although previous studies have shown that the WHOQOL-BREF can be applied across different diagnostic groups [20], some studies have indicated that modifications to the measurement model of the WHOQOL-BREF may be necessary to achieve sufficient model fit [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As to this last point, the complete profile and the wide set of information made available by the Rorschach test may be an important support to a psychological care plan, which can act in parallel with pharmacological therapy, only aiming at pain control. Literature and clinical experience with child and adolescent migraine converge to suggest that, as opposed to an aprioristic assessment of the painful symptom, detecting also dysfunctional psychological aspects through the interview with the patient and the parents represents an important turning point for improving the treatment possibilities and the quality of life of the patients themselves ( 67 69 ).…”
Section: Discussionmentioning
confidence: 99%